Does procedural fairness matter for drug abusers to stop illicit drug use? Testing the applicability of the process-based model in a Chinese context - Liu, Jianhong (Psychology, crime & law, 2020)
This study examined the influences of procedural fairness on Chinese drug users’ efforts to stop substance abuse, with a primary goal to test the applicability of the process-based model in the Chinese context. According to Tyler (1990, Why people obey the law. New Haven, CT: Yale University Press), the core theoretical argument underpinning the process-based model is that if citizens consider the police to be fair in using their powers, they will view the police as legitimate and accordingly cooperate with the police and comply with the law. Using data from a sample of 202 Chinese drug users, this study found that procedural fairness has an indirect effect on drug users’ efforts to stop illicit drug use. Specifically, procedural fairness used by the police increased Chinese drug users’ efforts to stop substance abuse through its prior effects on drug users’ perceptions of police trustworthiness. These findings provide some support for the key arguments of the process-based model of regulation, and have important implications for the direction of efforts to encourage desistance-related behavior among substance abusers.